Answer:
x = -2
y = 6
Step-by-step explanation:
i multiplied the 1st equation by 3 and the 2nd by 5 to get the y-terms to zero out
12x + 15y = 66
+ <u>35x - 15y = -160</u>
47x = -94
x = -94/47
x = -2
substitute -2 for 'x' to solve for 'y':
4(-2) + 5y = 22
-8 + 5y = 22
5y = 30
y = 6
Answer:
ye me too i cant answer thay
Are you sure you want ONLY the coefficient of b? If you expand this, you will have b in 3 of 4 terms.
According to Pascal's Triangle, the coefficients of (a+b)^4 are as follows:
1
1 2 1
1 3 3 1
1 4 6 4 1
So (a+b)^4 would be 1a^4 + 4a^3b + 6a^2b^2 + 4ab^3 + b^4
Here, you want (3 + b)^4. Here's what that looks like:
3^4 + 4[3^3*b] + 6[3^2*b^2] + 4[3*b^3] + 1[b^4]
Which coeff did you want?